Turbidity alters estuarine biodiversity and species composition. (11th November 2019) - Lunt, Jessica; Smee, Delbert L
Abstract: Turbidity is widely regarded for modulating primary production and influencing the distribution of submerged aquatic vegetation. Although less well studied, turbidity can also have significant effects on trophic interactions and food webs by modifying light penetration and scattering, influencing foraging ability of visual-hunting predators such as fishes. By interfering with visual foragers, turbidity may shift food webs towards predators that forage with other sensory modalities (e.g. chemoreception and mechanoreception), consequently altering food web structure. We analysed turbidity effects on estuarine community composition and biodiversity in the Gulf of Mexico by analysing an 18-year fisheries-independent data set and assessing communities inhabiting contemporary oyster reefs ( Crassostrea virginica ). In the long-term data set, elevated turbidity was associated with decreased fish species richness and diversity and higher abundances of benthic species that rely more on chemoreception for foraging and predator avoidance (e.g. crabs). High turbidity may provide a predation refuge for crabs and other benthic organisms that visually oriented fish prey upon. On oyster reefs, crabs readily consume suspension-feeding organisms including newly settled oysters and porcelain crabs ( Petrolisthes armatus ). Both were significantly less abundant in high turbidity. Human practices that increase turbidity may indirectly influence trophic interactions, species distributions, ecosystem function, and biodiversity.